2012
DOI: 10.4149/neo_2013_018
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs (cmiRNAs) as novel potential biomarkers for hepatocellular carcinoma

Abstract: Incidence and mortality associated with hepatocellular carcinoma (HCC) is rising throughout the world. Accurate, noninvasive biomarkers for the early detection of HCC are urgently needed to reduce worldwide morbidity and mortality related to HCC. MicroRNAs (miRNAs), 17- to 25-nucleotide noncoding RNAs that are frequently dysregulated in HCC, have shown great promise as tissue-based markers for HCC diagnosis and prognosis. Moreover, they are stably expressed in serum and urine, and these circulating microRNAs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(104 citation statements)
references
References 71 publications
4
100
0
Order By: Relevance
“…Understanding the expressional patterns of miRNAs enables their utilization therapeutically, i.e. for diagnosis, prognosis and target therapy [94,95]. Prognostic and biological roles of miR-155 have been evaluated in individual studies and meta-analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding the expressional patterns of miRNAs enables their utilization therapeutically, i.e. for diagnosis, prognosis and target therapy [94,95]. Prognostic and biological roles of miR-155 have been evaluated in individual studies and meta-analyses.…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of and mortality associated with hepatocellular carcinoma are increasing worldwide, and accurate, noninvasive biomarkers for the early diagnosis of HCC are urgently needed to reduce HCC-related morbidity and mortality (24 ). Recently, we developed an online trapping/ capillary hydrophilic-interaction liquid chromatography/ insource fragmentation/tandem mass spectrometry system for HCC detection by quantifying 5-methylcytosine (5-mC) and 5-hydroxymethylcytosine (5-hmC) in genomic DNA from HCC tumor samples.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have confirmed its association with advanced clinical stages of cancer, tumor metastasis, and poor prognosis. Several genes associated with tumor growth and metastasis, such as tumor suppressor tropomyosin 1 (TPM1), programmed cell death 4 (PDCD4), TIMP metallopeptidase inhibitor 3 (TIMP3), and phosphatase and tensin homolog (PTEN), have been proved to be targeted by miR-21 (Meng et al, 2007;Zhu et al, 2007;Frankel et al, 2008;Qi et al, 2013). The overexpression of miR-21 in tumor cells could alleviate their function in 'suppressing' cell apoptosis and death.…”
Section: Mir-21mentioning
confidence: 99%